Psychological Toll of COVID-19 Communication Patterns in Malawi - Mhagama, Peter (Taylor & Francis, 2023)
Utilising focus group discussions and face-to-face interviews with selected media managers and reporters, this chapter discusses the psychological effects of COVID-19 information dissemination on emotional well-being in Malawi. Whenever there is a pandemic, people respond differently due to the varied information they receive on the causes, effects, spread, and associated preventive measures. How people respond to the information they receive about the disease could have psychological effects on their mental well-being, such as anxiety and emotional distress, which could further affect how they adhere to the preventive measures and how they might react after contracting the disease. Studies have shown that psychological factors could also affect how a pandemic is managed and how people cope with infection and the fear of death. This chapter argues that infodemics, misinformation, and disinformation about COVID-19 created panic, fear, and anxiety among the people in Malawi. The chapter concludes that these effects and the people’s reaction to infodemics, misinformation, and disinformation were typical, given the nature of the disease and its dramatic effect.
Keywords: Covid-19; Malawi; Communication